Propaganda leaflets and Cold War frames during the Korean War - Hong, Seong Choul (Media, War & Conflict, 2018)
In the history of world wars, the Korean War (1950–1953) was not a forgotten war but the apogee of a propaganda war. By analyzing the contents of propaganda leaflets distributed during the Korean War, this study explored which frames were dominantly employed. The resulting findings were that the frames of ‘demoralization’ (25.7%) and ‘encouraging surrender’ (24.4%) were the most frequently used during the overall war period. Furthermore, the dominant frames varied depending upon the target audiences and language used. In terms of functional frames, the leaflet messages corresponded to definition and causal interpretation (22.8%), moral judgement (26.2%) and solution (49.9%). Interestingly, Chinese and North Korean leaflets preferred the imperialist frame to the Cold War frame even though the US and South Korean leaflets more heavily used the Cold War frame when they referred to foreign troops. Moreover, thematic frames (91.4%) were more widely used than episodic frames (8.6%) in the samples.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzUwNjM1MjE3Njk4NTA0